Core-shell structured α-AlH3/Fe2O3 thermite with improved heat-release and combustion performance - Jiashuai Wang; Bo Wu; Lingfeng Yang; Yuan Bian; Renjie Li; Ke Zeng; Juan Zhu; Liangyou Zhao; Jinpeng Shen; Chonghua Pei (FirePhysChem)
Thermites are widely used in propellants, explosives and ignition materials because of their high heat release rate and good combustion efficiency. Structural control over thermites to achieve improved performance leads to a promising research area. Among these, core-shell structured composites have attracted wide attention due to their excellent properties and close contact among components. Herein, core-shell structured α-AlH3/Fe2O3 thermites were prepared, which exhibit high heat-release and excellent combustion performance. At an equivalence ratio of 2.0, the core-shell structured α-AlH3/Fe2O3 has the most heat release (1213.8 J/g) and the lowest reaction activation energy (147.5 kJ/mol). The ignited combustion performance of α-AlH3/Fe2O3 was notably strengthened by the shorter ignition delay period (11 ms). Interestingly, the core-shell structured α-AlH3/Fe2O3 was less sensitive to electrostatic discharge, which suggests that the core-shell structured α-AlH3/Fe2O3 reaches the goal of high energy release and electrostatic safety. The core-shell thermite system with α-AlH3 as metal fuel could provide an efficient alternative to hunt for thermites with high reactivity.